Implementasi QS. Al-Ahzab Ayat 59 dalam Praktik Berpakaian Muslimah: Kajian Living Qur'an di Desa Mekar Sari, Deli Tua - Khoirotun Nisah Br. Munthe; Muhammad Ali Azmi Nst (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine Muslim women's understanding of Qur'an Surah Al-Ahzab verse 59 and their practice of dressing based on the verse in Neighborhood III of Mekar Sari Village, Deli Tua District. This research employed a qualitative approach using field research. Primary data were collected through questionnaires distributed to 30 respondents, while secondary data were obtained from the Qur'an, books, and relevant scientific journals. The data were analyzed descriptively using a qualitative approach by classifying the findings into good, fair, and poor categories. The findings indicate that the respondents' understanding of Qur'an Surah Al-Ahzab verse 59 falls into the good category, while their practice of Muslim women's dress falls into the fair category. The study also reveals that most respondents understand the content of the verse, but not all have fully implemented its teachings regarding Islamic dress in their daily lives. This research concludes that the implementation of Qur'an Surah Al-Ahzab verse 59 as a form of Living Qur'an is reflected in the understanding and dressing practices of Muslim women in Neighborhood III of Mekar Sari Village.